A hydrophobic anchor mechanism defines a deacetylase family that suppresses host response against YopJ effectors - Marco Bürger (Nature Portfolio, 2017)
A subset of α/β hydrolases is known to suppress the pathogen-triggered hypersensitive response (HR) in plants, but their mechanism of action remains unclear. The authors present two crystal structures and functional analyses of these enzymes, showing that HR is suppressed by a previously unknown family of deacetylases.